Exploring Bacopa monnieri phytochemicals as potential RSV inhibitors: An in-silico analysis of key compounds against fusion and glycoprotein targets - Pooja Yadav; Siddharth Singh; Priyanshi Dwivedi; Mala Trivedi; Aditi Singh (Microbes and Infectious Diseases, 2025)
Background: Respiratory Syncytial Virus (RSV), also known as Human Orthopneumovirus, is a significant cause of lower respiratory tract infections worldwide, particularly impacting children. Despite the urgent need, effective vaccines and treatments remain limited. Natural products, especially phytochemicals from medicinal plants, have recently gained attention as potential sources of antiviral agents. Methods: We investigated phytochemicals from Bacopa monnieri, an herb with a long-standing history in traditional medicine, for their antiviral potential against RSV. Using in-silico molecular docking, six key phytochemicals (Betulinic acid, Jujubogenin, Bacogenin-a1, Pseudojujubogenin, Bacosine, and Ebelin lactone) were selected based on Lipinski’s rule and binding affinity toward RSV's essential proteins, the Fusion (F) and Glycoprotein (G). Results: Docking results revealed that Jujubogenin exhibited the strongest binding affinity, with scores of -9.4 kcal/mol for the F protein and -8.7 kcal/mol for the G protein, suggesting its potential to inhibit RSV entry and infection processes. Conclusion: This study demonstrates that phytochemicals from Bacopa monnieri may offer a promising direction for developing natural therapeutics against RSV